ANALISIS ORGANIZATIONAL CITIZENSHIP BEHAVIOR PEGAWAI BAGIAN RAWAT INAP PADA RUMAH SAKIT DI KOTA PEKANBARU - Iskandar, Iskandar (Sekolah Tinggi Ilmu Ekonomi Riau, 2016)
This research was conducted at Ibnu Sina Hospital Pekanbaru located on the street Jalan Melati No. 60 Pekanbaru. The purpose of this study to determine and analyze the influence of individual characteristics, organizational climate and organizational commitment either simultaneously or partially on Organizational Citizenship Behavior on the part of employees inpatient Ibnu Sina Hospital Pekanbaru. To achieve these objectives the research is done by using the sample of 61 people, using the method of accidental sampling. Data analysis method using simultaneous test and partial test (multiple linear regression analysis with SPSS Windows version 20). Partial test results partial on variable individual characteristics, organizational climate and organizational commitment has a positive and significant impact on Organizational Citizenship Behavior on the part of employees inpatient Ibn Sina Hospital Pekanbaru. R. Square value (R2) of 0778 (77.8%) explained that the Organizational Citizenship Behavior in the employee section inpatient Ibn Sina Hospital Pekanbaru can be explained by factors of individual characteristics, organizational climate and organizational commitment which amounted to 77.8%. Recommendations to the authors propose is expected to Ibn Sina Hospital Pekanbaru to further improve the organizational commitment variables to be improved is because employees feel Ibnu Sina Hospital Pekanbaru must support what is done by the employees